Role of tumor-associated macrophages in hepatocellular carcinoma: impact, mechanism, and therapy - Zhang, Yinqi; Han, Guoyong; Gu, Jian; Chen, Zhiqiang; Wu, Jindao (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is a highly frequent malignancy worldwide. The occurrence and progression of HCC is a complex process closely related to the polarization of tumor associated macrophages (TAMs) in the tumor microenvironment (TME). The polarization of TAMs is affected by a variety of signaling pathways and surrounding cells. Evidences have shown that TAMs play a crucial role in HCC, through its interaction with other immune cells in TME. This review summarizes the origin and phenotypic polarization of TAMs; potential impacts of TAMs in HCC and their mechanisms and potential targets for HCC immunotherapy.